A Many-Component Cosmic Fluid with a Dynamic Dark Energy Term for the Accelerating Universe - Sivakumar, C. (Journal of Scientific Research, 2026)
Earlier studies have shown that in a two-component model of the universe with matter and the running vacuum energy, either eternal deceleration or acceleration is produced in the absence of a bare constant in the density of the running vacuum. Here, it is analytically solved for the Hubble parameter, in a spatially flat Friedmann universe with dark energy and matter as components, and the solution traces the evolutionary path from the prior decelerated to the late accelerated epoch. But along with the additive constant, equivalent to a cosmological constant, the model predicts a late time exponential acceleration in the expansion of the universe, and in the far future of the evolution it tends to de Sitter universe with deceleration parameter approaches -1. On contrasting the model with the cosmological data, it is favoured to the low value of present Hubble constant as measured from the CMB data.